2002
DOI: 10.1159/000058418
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders among Patients Undergoing Hemodialysis Therapy

Abstract: We examined the incidence rates of psychiatric disorders in end-stage renal failure patients on hemodialysis (HD) based on 4-year long-term follow-up. Among various psychiatric disorders, the frequency of three psychiatric disorders, dementia, delirium, and major depression, was relatively high. One-year incidence rate of whole psychiatric disorders was 10.6% (7.1% in non-aged and 13.7% in aged). One-year incidence rate of dementia in aged patients was 4.2% (dementia of the Alzheimer’s disease, 0.5%; multi-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
2
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 1 publication
0
69
2
8
Order By: Relevance
“…Individuals with CKD have an increased risk for stroke (20), an established risk factor for cognitive impairment and dementia in the general population (21). In previous studies, CKD and ESRD were more strongly associated with vascular dementia than Alzheimer's dementia (1,4), suggesting that an increased burden of cerebrovascular disease may explain the association between CKD and dementia. In this study, adjustment for incident stroke only modestly attenuated the elevated risk for cognitive impairment for participants with an eGFR Ͻ45 ml/min per 1.73 m 2 and did not change the effect estimates for those with an eGFR 45 to 60 ml/min per 1.73 m 2 , suggesting that factors other than the severity of cerebrovascular disease are involved in the pathogenesis of cognitive impairment in CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with CKD have an increased risk for stroke (20), an established risk factor for cognitive impairment and dementia in the general population (21). In previous studies, CKD and ESRD were more strongly associated with vascular dementia than Alzheimer's dementia (1,4), suggesting that an increased burden of cerebrovascular disease may explain the association between CKD and dementia. In this study, adjustment for incident stroke only modestly attenuated the elevated risk for cognitive impairment for participants with an eGFR Ͻ45 ml/min per 1.73 m 2 and did not change the effect estimates for those with an eGFR 45 to 60 ml/min per 1.73 m 2 , suggesting that factors other than the severity of cerebrovascular disease are involved in the pathogenesis of cognitive impairment in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…T he prevalence of cognitive impairment and dementia in ESRD is more than double that of the general population (1)(2)(3). However, the reasons for this high rate remain uncertain.…”
mentioning
confidence: 99%
“…I noen få har man også inkludert pasienter i peritonealdialyse. Et fåtall av studiene har kontrollgrupper, og kun i to av studiene på dialysepasienter har man fulgt kognitiv funksjon over tid (5,6).…”
Section: Forekomst Av Kognitiv Sviktunclassified
“…De viktigste nyere studiene (gjort etter 1995, med antall pasienter ≥ 30 og med gjennomsnittsalder på pasientene ≥ 55 år) er vist i tabell 1 (5,(7)(8)(9)(10)(11).…”
Section: Forekomst Av Kognitiv Sviktunclassified
“…Indeed, several studies have reported end-stage renal disease as a predisposing factor for dementia [1,2]. This high burden is said to be poorly recognized by nephrologists who are the primary physicians caring for patients with CKD [3].…”
Section: Introductionmentioning
confidence: 99%